5(x+1)=2(3x-4)

Simple and best practice solution for 5(x+1)=2(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+1)=2(3x-4) equation:


Simplifying
5(x + 1) = 2(3x + -4)

Reorder the terms:
5(1 + x) = 2(3x + -4)
(1 * 5 + x * 5) = 2(3x + -4)
(5 + 5x) = 2(3x + -4)

Reorder the terms:
5 + 5x = 2(-4 + 3x)
5 + 5x = (-4 * 2 + 3x * 2)
5 + 5x = (-8 + 6x)

Solving
5 + 5x = -8 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + 5x + -6x = -8 + 6x + -6x

Combine like terms: 5x + -6x = -1x
5 + -1x = -8 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -1x = -8 + 0
5 + -1x = -8

Add '-5' to each side of the equation.
5 + -5 + -1x = -8 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = -8 + -5
-1x = -8 + -5

Combine like terms: -8 + -5 = -13
-1x = -13

Divide each side by '-1'.
x = 13

Simplifying
x = 13

See similar equations:

| 43=2x-3 | | -8(6w-7)=50 | | 7=6x-86 | | 13=44 | | 7=5x-46 | | 2x+20+4x=0 | | p/3=2/6 | | 9-3r=-4r | | 1m+3=9+3m | | -7x+17-30=71 | | 6d+4+5d+2d=58 | | 6g-8=7g | | 40+(3x)=12-x | | 3x+3(x+5)=51 | | -4u(u-9)(u+2)=0 | | h=-2d^2+100 | | -9(n-7)=-7+5n | | (44xy)(-1/11) | | 4(v+6)(-v+5)=0 | | K/16=13 | | 4X-X=6+2 | | -7/10=1/2 | | 10/15=2/? | | 12x^2+16x=x^4 | | 0=23.0+(-2.96)t | | 13=-6m+6-5 | | (2y-1)(8-y)=0 | | 20+(3x)=32-x | | -8x+3=-3-6 | | 15+(5-x)=30/x | | 3m/2 | | 4-1/(2(x^1/2))=0 |

Equations solver categories